Electrochemical Oxidations of p-Doped Semiconducting Single-Walled Carbon Nanotubes - Huaping Li; Lili Zhou (Journal of Nanotechnology)
Two oxidation peaks at 0.99, 1.48 V versus Fc/Fc+ appear in the cyclic voltammograms of a series of defect-site functionalized SWNTs in methylene chloride solution in the presence of ferrocenes. These two peaks are demonstrated to be the electrochemical responses to the independent oxidation of v1 and v2 valence bands of p-doped semiconducting SWNTs.